Impact of adopting improved Arabica varieties on the livelihood of organic coffee producers’ of Ethiopia: Continuous treatment approach - Negussie Zeray Gebru; Tasew Tadesse; Wajana Wae (Cogent Food & Agriculture)
The study evaluated the impact of adopting improved coffee Arabica on organic coffee producers’ households’ livelihoods by employing data obtained from 120 coffee producer households in the Gedeo zone. The generalised propensity-score matching methodology is used to analyse the data. The approach was used to match families with similar variables and varying levels of enhanced Arabica coffee adoption intensity. The technique proved efficient in elucidating non-linear causal links between adoption intensities, dosages, and outcome variables. The average dose-response or impact function was calculated by averaging consumer expenditure, household per capita income, and calorie intake per AE at various levels of adoption intensities. The result showed that initially, coffee production had a negative impact on kilocalories per adult equivalent (AE) but turned positive following an adoption dose that reached the optimum. The improved Arabica coffee varieties’ optimal adoption dose is 71.42%, and the equivalent annual household calorie consumption is 2,384.80 kilocalories per AE. However, the impact of coffee Arabica adoption on consumption expenditure was initially positive, but it turned negative after the adoption dose reached its optimum. The level of optimum adoption is 28.41, and the annual household consumption expenditure was 13704 Ethiopian Birr. Furthermore, at an optimum level of 83.66%, the intensity of adoption and income of coffee producers had a positive impact. In this context, policies that promote the efficiency of coffee production and minimize the barriers to farmer adoption provide the most optimal land allocation for improved technology and, in doing so, improve the lives of households.